Unusual Signs and Symptoms in Internal Medicine. - Gallo, Vittorio (SEEd Srl, 2011)
This book aims at providing a support in the interpretation of the most unusual signs and symptoms that can be encountered in the clinical practice. Each sign is described in concise way (one sign/one page): a full description of the symptoms as experienced by the patient is given, followed by its clinical meaning, the diagnosis and therapeutic approach.